Influences of Social Structure on the Diffusion and Adoption of Recommended Goat Husbandry Practices - Pattamarakha, Kriengsak; Tanapanyarachwong, Jitpaka; Saithanoo, Somkiat (Kasetsart Journal of Social Sciences, 1996)
This study aims to investigate pattern of the diffusion of goat raising of southern Thai farmers and their uses of recommended goat husbandry practices, to compare the characteristics of farmers in more and less developed villages and to identify economic, social, communicative and psychological factors affecting the adoption of recommended goat husbandry practices. The study revealed that most farmers used very few recommended practices as they perceived that their goats were in good health. Although most farmers had good knowledge of recommended practices, these practices were perceived to be unnecessary. This perception was observed by farmers in both more and less developed villages. Although farmers in more developed villages had a higher income and had a better standard of living than those in less developed villages, no statistical difference was observed in the use of recommended goat husbandry practices between the two groups. In correlation analysis, socio-economic factors - income, standard of living, number of goats, leadership status, social participation, knowledge of goat husbandry, awareness of community leaders, urban contact and degree of modernization - were found to correlate with the degree of adoption of recommended goat husbandry practices.